Vigilant care: constructive dialogues and relational responsibility in violent contexts - Marlene Magnobosco Marra (Revista Brasileira de Psicodrama, 2020)
This is a qualitative exploratory study by the “Assistance and Vigilance Research Program on Violence”, focusing on a group of seven sexual abuse survivors and their mothers. The study’s objective is to develop a caretaker protocol for Parent Vigilant Care. Observers register protocol sessions by themes evolving within the action group. The information is organized into categories: 1) Hidden pain, 2) Caring is protecting, and 3) Breaking through isolation. Observation and conclusions focus on the following: 1) The disconnect revealed by mothers and daughters on the role of mothers in their daughters’ lives, 2) The potential for recovery of affective relationships, 3) Respect development for a horizontal or equalization of power, 4) The return or rescue of a mother’s competency and authority.